Cognitive interdependence and the everyday expression of commitment. (March 2020) - Davis, Bret A.; Weigel, Daniel J.
Based on interdependence theory, this study expands the work on cognitive interdependence—viewing a relationship as a pluralistic collective—by testing the proposition that cognitive interdependence is connected with everyday expressions of commitment. A sample of 275 individuals in romantic relationships completed an online survey. Results revealed that cognitive interdependence is characterized by greater inclusion of partners into self-concepts, more positive thoughts about the relationship, and viewing the relationship as central to one's life. Further, results showed that cognitive interdependence is a critical linchpin mechanism linking relationship commitment with everyday expressions of commitment. The findings are discussed in terms of the importance of cognitive interdependence for understanding commitment and pro-relationship behavior.